ANALYSIS OF THE PSYCHIATRIC HOSPITALIZATIONS THROUGH THE SUS IN PIAUÍ, BRAZIL, FROM 2008 TO 2020 - Melo, Francisca Carolina Pimentel; Oliveira, Andressa Suelly Saturnino de; Oliveira, Ana Karla Sousa de; Melo Júnior, Eugênio Barbosa de; Campelo, Lany Leide de Castro Rocha; Ibiapina, Aline Raquel de Sousa; França, Luara da Costa (Cogitare Enfermagem, 2022)
Objective: to analyze the behavior of data referring to psychiatric hospitalizations in Piauí between 2008 and 2020. Method: an ecological study conducted with secondary data referring to psychiatric hospitalizations between 2008 and 2020 in Piauí, obtained from the Hospital Information System/DATASUS. Descriptive and linear regression analyses were performed. Results: a total of 40,608 psychiatric hospitalizations were found. The main causes were schizophrenia (17,877) and mood disorders (8,239). Mental retardation and schizophrenia presented higher costs and mean hospitalization times. A reduction in the number of hospitalization was recorded from 2009 to 2012 and there was increase between 2016 and 2019, regardless of age and gender. Hospitalizations were more frequent among adults (94.4%) and men (62.4%). Conclusion: the reduction in the number of psychiatric hospitalizations in Piauí from 2009 to 2012 coincides with the closing of the state's psychiatric hospital and with the strengthening of the Psychosocial Care Network. The data reflect previous mental health policies and allow planning health strategies.